Information design in nutrition public policies: contributions to food and beverage labeling in Brazil - Spinillo, Carla Galvão; Rojas, Carlos Felipe Urquizar; Hammerschmidt, Christopher (InfoDesign, 2025)
Public policies are essential to improve the health conditions of the population. Malnutrition caused by the increase in the consumption of ultra-processed foods and drinks with excess sodium, sugars, and fat is a public health problem. In this scenario, nutritional labeling of industrialized products becomes strategic to inform the population about health risks of such products, and in helping them make informed healthy food choices. This article presents contributions from the field of information design to nutritional labeling, through an experience report of the Information Systems Design Laboratory (LabDSI/UFPR). The role and participation of the Laboratory in regulatory discussions and proposals for nutrition labeling systems in Brazil and Mercosur is highlighted. Finally, the relevance of information design to health policies and the need for further research in nutritional labeling are pointed out.